The Germanic Tribes, the Gods and the German Far Right Today - Schuppener, Georg 1968- (Routledge Studies in Fascism and the Far Right, 2022)
The Germanic Tribes, the Gods and the German Far Right Today deals with the question of how right-wing extremists in German-speaking countries adapt and adopt elements from the history, culture, and mythology of the Germanic tribes. It provides the first in-depth study of the adoption of these historical motifs by right-wing extremists. Using linguistic and historical perspectives, and drawing on both publicly accessible material and sources gathered by the intelligence services, the book delineates the influence and impact of Germanic tribal history and culture within extremist subcultures. The author demonstrates that references to the Germanic peoples, their history, culture, and mythology, are even more widespread among contemporary right-wing extremists than they were in the interwar National Socialist era. This book will be of interest to researchers of right-wing extremism, German politics, and social movements